‘Awakening the Sleeping Beauty’: Brazil’s vision of a modern agriculture and the Role of the Office of Inter-American Affairs under Nelson Rockefeller - Prutsch, Ursula (Diálogos Latinoamericanos, 2022)
This article discusses the role of the U.S. war institution Office of Inter-American Affairs (1940-45) in the modernization policies of Brazil during the first government of Getúlio Vargas. The first section analyses - based on Brazil’s modernization utopias since the late 19th century - the concept of nation-building with its “March to the West”, the integration of the hinterland into the nation. The second section describes the structure and strategies of the Office of Inter-American Affairs (OIAA) and its goals to mobilize as many natural resources for the war effort as possible. Providing food supply for Allied Forces and US troops in Brazil, and for miners and rubber collectors comprised the most eminent tasks of the OIAA, whose agricultural policies in Brazil are the topics of the third section, while the last section highlights that the US policies of agricultural modernization in Brazil went far beyond World War II.